Relationship between Authoritative Parenting Style and Preschools Prosocial Behavior - Nurul Arifiyanti (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2019)
Preschools behavior must be developed since early of children ages. It is believed to affects their further characters. It plays an important role in their habit, building interaction, and character development. Childrens behavior is influenced by the habit which is done by the people around of them, like parent. Hence this study proposes parenting style on preschools prosocial behavior. Those effects are likely varied from home. Participating preschool students (N= 61) during two weeks in January 2017 who had a mean age of 5.14 years. The data were obtained using questionnaire and observation sheet. A quantitative research method was use to collection, analysis and interpretation of data. According to the result, there was not significant positive correlation between authoritative parenting style and preschool prosocial behavior. Accordingly, it can be concluded that there were alternative factors such as teacher-classmates, teacher-child relation, and childrens moods and feelings.